2019
DOI: 10.1038/s41598-019-55536-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of deep learning-based algorithm for detection of ileocolic intussusception on abdominal radiographs of young children

Abstract: The purpose of this study was to develop and test the performance of a deep learning-based algorithm to detect ileocolic intussusception using abdominal radiographs of young children. For the training set, children (≤5 years old) who underwent abdominal radiograph and ultrasonography (US) for suspicion of intussusception from March 2005 to December 2017 were retrospectively included and divided into control and intussusception groups according to the US results. A YOLOv3-based algorithm was developed to recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Kim et al reported that drawing rectangular ROI indicators on abdominal radiographs could allow deep learning-based algorithms to aid in screening for right upper quadrant ileocolic intussusception in young patients. According to a 75-image internal validation test, the sensitivity and specificity values of their algorithm were 0.76 and 0.96, respectively, which are better than those of a radiologist who was found to have sensitivity and specificity values of 0.56 and 0.92, respectively 23 . In our study, we drew a rectangular ROI that encompassed the entire abdomen; the ranges of the sensitivity and specificity values after conducting training and internal tests using two data sets were 0.913-0.943 and 0.851-0.905, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Kim et al reported that drawing rectangular ROI indicators on abdominal radiographs could allow deep learning-based algorithms to aid in screening for right upper quadrant ileocolic intussusception in young patients. According to a 75-image internal validation test, the sensitivity and specificity values of their algorithm were 0.76 and 0.96, respectively, which are better than those of a radiologist who was found to have sensitivity and specificity values of 0.56 and 0.92, respectively 23 . In our study, we drew a rectangular ROI that encompassed the entire abdomen; the ranges of the sensitivity and specificity values after conducting training and internal tests using two data sets were 0.913-0.943 and 0.851-0.905, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…As mentioned in related work, there are several other technical options to achieve a similar goal of automatic diagnosis of certain disease from radiograph images, including feature point, active shape model, and full machine learning, which not only recognizes region of interest but also performs the measurements automatically [ 11 , 12 , 18 ]. We used a two-phase algorithm, which separated machine-learning-based region of interest recognition and parameter measurement because doing so has several advantages compared with the other options.…”
Section: Discussionmentioning
confidence: 99%
“…The femoral axis and tibial axis will also be determined. Then, YOLOv3 ( https://pjreddie.com/darknet/yolo/ ), an object-detection tool based on machine learning, is used to segment the knee joint from the original image [ 11 , 12 ]. A median filter, i.e., block-matching and three-dimensional (BM3D) filter, and histogram equalization will be applied to the segmented image for enhancement and removal of noise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kim et al [ 22 ] have evaluated diagnostic performances of artificial intelligence (AI) and a deep learning-based algorithm for detecting ileocolic intussusception using AXR. Our study was meaningful as a pilot study for developing AI deep learning algorithm, since it determined AXR's associations with recurrent intussusceptions after therapeutic reduction.…”
Section: Discussionmentioning
confidence: 99%